Metabolomic Study of Andrographis paniculata Using Fourier Transform Infrared Spectroscopy and Gas Chromatography-Mass Spectrometry - Yustawan, Dandy Arif; Apriliani, Firli Triayu; Farmasari, Novan Visia; Rofida, Siti (Universitas Muhammadiyah Yogyakarta, 2026)
Andrographis paniculata contains bioactive compounds with anticancer, hepatoprotective, antibacterial, antidiabetic, antihypertensive, analgesic, and anti-inflammatory properties. Key compounds include andrographolide, paniculide, farnesol, flavonoids, saponins, alkaloids, phenols, and tannins. Environmental and geographic factors influence the composition of these compounds, thereby altering metabolite profiles. This study used FTIR and GC-MS methods in a non-targeted metabolomics approach to identify and analyze the metabolite diversity of Andrographis paniculata from different regions of Java Island. The FTIR analysis identified functional groups associated with secondary metabolites, including tannins, flavonoids, andrographolide, saponins, alkaloids, and triterpenoids. GC-MS profiling identified 43, 46, and 49 metabolites in West Java, Central Java, and East Java samples, respectively, with fatty acids and fatty acid esters as the dominant classes. PCA clearly separated Central Java samples from the other two regions, while ANOSIM confirmed significant differences in chemical composition among the groups. Overall, the findings demonstrate that geographical origin strongly influences the secondary metabolite composition of A. paniculata, with Central Java exhibiting the most distinct profile.